FRI0394 Diagnostic Accuracy of Salivary Gland Ultrasonography in Patients with Systemic Sclerosis and Associated Sjögren's Syndrome. (9th June 2015) - Baldini, C.; Luciano, N.; Ferro, F.; Sernissi, F.; Martini, D.; Cagnoni, M.; Mosca, M.; Bombardieri, S.
Abstract : Background: Systemic sclerosis (SSc) is a multisystem disease in which sicca symptoms and particularly oral manifestations are quite common. The prevalence of an associated Sjögren's syndrome (SSc-SS) in SSc patients ranges from 20 to 40% whereas in the vast majority of the cases sicca symptoms can be attributed to a fibrosis of the exocrine glands. Recently, a growing interest has arisen for salivary gland ultrasonography (SGUS) as an useful tool for the diagnosis of primary SS. Nonetheless, data on the utility of the SGUS in patients with SSc and suspected associated SS are limited. Objectives: To assess the diagnostic accuracy of salivary gland ultrasonography (SGUS) in patients with SSc and suspected concomitant SS Methods: From Jan 2014 to November 2014 consecutive, unselected patients with SSc were systematically evaluated for sicca symptoms by using the AECG questionnaire. Patients with suspected SS underwent a complete diagnostic work-up. SGUS was carried out by the same radiologist blinded to the diagnosis and the following US parameters were recorded: size, parenchymal echogenicity and inhomogeneity in the parotid and submandibular glands on both sides, number and location of hypo or anechoic area, presence of lymp nodes and calcifications. A modified version of the De Vita score was adopted to grade the echostructure alterations of the salivary glands. Comparison were made using parametric Student's t test and non-parametric Mann-Whitney U test as applicable. Dichotomous variables were compared using contingency table analysis and Fisher's Exact test. Spearman's rank correlation was applied for detecting correlations between SGUS score and different study parameters. Results: Of 145 patients evaluated for sicca symptoms, 47 females were enrolled. The sample had a mean age (S.D) of 68 (14) yrs, and a mean disease duration (S.D) of 4 (4) yrs. Anticentromere antibodies were detected in 42/47 of the patients. A diagnosis of SSc-SS was made in 32/47 (68%) of the cases. No differences between SSc and SSc-SS patients were observed with respect to gender, age and duration of dry-mouth and dry-eye related symptoms. Patients with SSc-SS showed a higher SGUS score (mean (SD)=1.9 (1.9) vs 0.2 (0, 4), p<0.0001). Isolated or localized hypoechoic areas were observed also in a minority of patients with SSc alone (2/15). However, diffuse or scattered hypoechoic areas were detected exclusively in patients with SSc-SS. A strong correlation was found between the grade of the echostructure alteration of the parotid and of the submandibular glands (r=0.754, p<0.0001). We also observed that the fibrosis of the submandibular glands was significantly higher in SSc-SS patients (84% vs 53%, p=0.04). No differences between SSc-SS and SSc patients were detected regarding parotid fibrosis, size of the glands, presence of lymph nodes or calcifications. Overall SGUS showed a sensitivity (SE) of 66%, a specificity (SP) of 87%, a positive predictive value (PPV) of 91% and a negative predictive value (NPV) of 54% for SS diagnosis. Conclusions: This study demonstrated the utility of SGUS for the diagnosis of SS in the context of SSc, thus encouraging the use of SGUS in clinical practice. Disclosure of Interest: None declared